2021
DOI: 10.52587/jems020102
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Money Supply on Inflation in Pakistan

Abstract: This study examines the relationship between inflation, Money supply, interest rate and unemployment in Pakistan using annual time series data from 1987 to 2019. Inflation is used as the dependent variable and money supply (M2), unemployment and interest rate as the independent variable. Discount rate is used as the proxy of the interest rate. The results of ADF unit root test shows that variables have different order of integration. The study used ARDL cointegration approach to test the long run and short run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…This means that the budget deficit is a negative function of inflation in Nigeria, and that increasing the fiscal deficit may lessen the country's inflationary tendencies. This finding is consistent with the findings of Hassan, Zia, and Baig (2020), who evaluated the influence of money supply and inflation on Pakistan's fiscal deficit and discovered a negative link between inflation and fiscal deficit. This result, however, contradicts the findings of Ebipre and Amaegberi (2020), who investigated the relationship between money supply and inflation rate in Nigeria from 1981 to 2017.…”
Section: 1: Discussion Of Findingssupporting
confidence: 92%
See 1 more Smart Citation
“…This means that the budget deficit is a negative function of inflation in Nigeria, and that increasing the fiscal deficit may lessen the country's inflationary tendencies. This finding is consistent with the findings of Hassan, Zia, and Baig (2020), who evaluated the influence of money supply and inflation on Pakistan's fiscal deficit and discovered a negative link between inflation and fiscal deficit. This result, however, contradicts the findings of Ebipre and Amaegberi (2020), who investigated the relationship between money supply and inflation rate in Nigeria from 1981 to 2017.…”
Section: 1: Discussion Of Findingssupporting
confidence: 92%
“…The study found that M2 impact positively and significantly on inflation. Masood, Mubashar and Mirza (2020) used data from 1990 to 2017 to analyze the connection among inflation, fiscal deficit and money supply in Pakistan. The collected data was analyzed using regression analysis and cointegration tests and the result disclosed that inflation is positively connected to money supply and negatively related fiscal deficit in Pakistan.…”
Section: Empirical Reviewmentioning
confidence: 99%